DFT Insights into the Structural, Mechanical, Electronic and Optical Properties of Novel InZnCl3 and InCdCl3 Chloro-Perovskites - Pingak, Redi Kristian; Ngara, Zakarias Seba; Johannes, Albert Zicko; Bukit, Minsyahril; Tanesib, Jehunias Leonidas; Nitti, Fidelis; Sianturi, Hery Leo; Pasangka, Bartholomeus (Universitas Gadjah Mada, 2024)
The ABX3 perovskite materials have recently emerged as one of the most promising materials for optoelectronic applications. In the present study, novel perovskites in the form of InZnCl3 and InCdCl3 are computationally investigated to determine their key characteristics, including structural, mechanical, electronic, and optical characteristics. These characteristics were evaluated using the density functional theory (DFT) implemented in the quantum espresso code. The results indicated that both materials exhibit chemical, dynamic, and mechanical stability. Moreover, these perovskites are predicted to be ductile, rendering them suitable for a broad array of optoelectronic applications, including solar cells. The electronic band structure and the density of states of the materials revealed their characteristics as indirect semiconductors with band gap energy values of 0.96 eV for InZnCl3 and 1.83 eV for InCdCl3 perovskites. The optical properties calculations also unveiled that these perovskites possess strong absorption in the visible-ultraviolet spectrum (up to 106 cm−1) and low reflectivity. The calculated refractive index and extinction coefficient of the compounds were also predicted in this study. These collective findings strongly suggest the potential applications of these novel materials in optoelectronic devices.